Question 1:
Consider the equation [tex](3x-1)^2 = 5[/tex]
Taking square root on both the sides of the equation, we get
[tex](3x-1) = \pm \sqrt{5}[/tex]
Consider [tex]3x-1 = \sqrt 5[/tex]
adding '1' to both sides, we get
[tex]3x = \sqrt 5 + 1[/tex]
Dividing by '3', we get
[tex]x = \frac{\sqrt5 + 1}{3}[/tex]
Consider [tex]3x-1 = - \sqrt 5[/tex]
adding '1' to both sides, we get
[tex]3x = - \sqrt 5 + 1[/tex]
Dividing by '3', we get
[tex]x = \frac{- \sqrt5 + 1}{3}[/tex]
So, the solution set for this equation is [tex]x = \frac{\sqrt5 + 1}{3}[/tex] and [tex]x = \frac{- \sqrt5 + 1}{3}[/tex].
Question 2:
Consider the equation [tex]x^2+5x+1 = 0[/tex]
We will use quadratic formula, we get
[tex]x = \frac{-5\pm \sqrt{5^2-4}}{2}[/tex]
[tex]x = \frac{-5\pm \sqrt{21}}{2}[/tex]
So, the solution set for this equation is [tex]x = \frac{-5+ \sqrt{21}}{2}, x = \frac{-5- \sqrt{21}}{2}[/tex].
Question 3:
Consider the equation [tex]x^2+5x+3=0[/tex]
By using the quadratic formula, we get
[tex]x = \frac{-5\pm \sqrt{5^2-12}}{2}[/tex]
[tex]x = \frac{-5\pm \sqrt{13}}{2}[/tex]
so, the solution set for this equation is [tex]x = \frac{-5+ \sqrt{13}}{2}, x = \frac{-5- \sqrt{13}}{2}[/tex].